A distributed-parameter electromechanical coupling model for a segmented arc-shaped piezoelectric energy harvester. (1st January 2021) - Zhou, Weijian; Wang, Biao; Lim, C.W.; Yang, Zhengbao
Highlights: Segmented arc-shaped piezoelectric energy harvester is proposed. A new distributed-parameter electromechanical coupling model is developed. The analytical solutions are validated with FEM and experiments. Energy harvester characteristics with optimal parameters to generate maximum output voltage of 50 V are fully investigated. Abstract: Advances in energy harvesting techniques, along with low-power electronic devices open up the possibility of developing self-powered engineering systems. Most existing energy harvesters are constructed with beams such as cantilevers, fully-clamped beams and buckled beams. Here we present an attempt to add a new design dimension to the piezoelectric energy harvesters (PEHs) by exploiting a curved-beam structure. This design will be shown to dramatically improve the contemporary harvester performance. To establish an analytical base for curved PEHs, we take a variable-curvature unimorph as the general modelling object and derive its governing equations based on the Timoshenko beam theory. Using the mode expansion method with the consideration of boundary conditions and continuous conditions, we present analytical solutions of the electrical and mechanical response of the PEH. The model developed is verified via the finite element method and it can accurately estimate the modal response of the curved PEH. Prototypes are fabricated and tested to validate the analytical model and solutions. Furthermore, we comprehensively analyzed the key parameter effects including the length of the straight beam, thickness ratio and Young's modulus on the performance of the PEH. The proposed analytical model provides an analytical guidance for composite arc-shaped PEHs with variable curvature and it also helps in the design and optimization of new PEHs.